Machine Learning and Deep Learning Using Python and TensorFlow - Kadre, Shailendra; Reddy Konasani, Venkata (McGraw-Hill's AccessEngineering., 2021)
This book provides you with an in-depth treatment of some advanced machine learning methods such as random forests, boosting, and neural networks.